Assessment and Feedback for Large Classes in Transnational Engineering Education: Student-Staff Partnership-Based Innovative Approach - Sajjad Hussain; Kelum A. A. Gamage; Wasim Ahmad; Muhammad A. Imran (MDPI AG, 2019)
Assessment and feedback (A&F) are two major components of any educational program and must be properly in place to ensure student learning and quality of experience. However, these important components come under severe challenges of meeting student expectations in the large class size context. When the program delivery relates to a transnational educational (TNE) scenario, the additional constraints on staff−student physical interaction, regional time differences and cultural background gaps introduce additional challenges: Conducting proper assessments and provide timely and constructive feedback to the students. In this paper, the authors propose a novel assessment and feedback framework which exploits having a large student number as a positive factor by introducing staff−student partnership to implement efficient assessment and feedback strategies. Authors propose to use students for peer-review, assessment design, evaluation rubric design and tutorial-based feedback. The students also take part in preparing feedback clusters based on which the instructor provides pseudo-personalised video feedback. Through feedback clusters, authors introduce the trade-off between individual feedback and generic feedback. The results of the study are particularly promising in terms of student satisfaction and learning enhancement.